CKD-5, a novel pan-histone deacetylase inhibitor, synergistically enhances the efficacy of sorafenib for hepatocellular carcinoma - Young Chang; Yun Bin Lee; Eun Ju Cho; Jeong-Hoon Lee; Su Jong Yu; Yoon Jun Kim; Jung-Hwan Yoon (BMC Cancer, 2020)
Abstract Background Histone deacetylase inhibitors (HDACIs) have distinctive epigenetic targets involved in hepatocarcinogenesis and chemoresistance. A recent phase I/II study reported the possibility of HDACI as a chemosensitizer in sorafenib-resistant patients. In this study, we evaluated whether CKD-5, a novel pan-HDACI, can potentiate the efficacy of sorafenib. Methods The anticancer effect of CKD-5 with and without sorafenib was evaluated in vitro using an MTS assay with human HCC cells (SNU-3058 and SNU-761) under both normoxic and hypoxic conditions. Microarray analysis was performed to investigate the mechanism of cell death, which was also evaluated by small interfering RNA (siRNA) transfection and subsequent immunoblot assays. In vivo experiments were conducted using two different murine HCC models. C3H mice implanted with MH134 cells and C57BL/6 mice implanted with RIL-175 cells were treated with weekly CKD-5 with and without sorafenib for 2 weeks. Results CKD-5 treatment significantly suppressed human HCC cell growth in both normoxic and hypoxic conditions. Microarray analysis and real-time PCR showed that CKD-5 treatment significantly increased peripherin expression in HCC cells and that downregulation of peripherin by siRNA decreased CKD-5-induced apoptosis. The combination of CKD-5 and sorafenib decreased cell viability more effectively than sorafenib or CKD-5 monotherapy in human and murine HCC cells. The effectiveness of the combination therapy was consistently demonstrated in the animal models. Histological and biochemical analyses demonstrated good tolerance of CKD-5 plus sorafenib in vivo. Conclusion CKD-5 may enhance sorafenib efficacy through epigenetic regulation. The combination of CKD-5 and sorafenib might be a novel therapeutic option for the treatment of HCC.